Industrial heritage and a matter of class: a memory lockout? - Stoler, Mariana (Huarte de San Juan. Geografía e Historia, 2025)
A recognition of the fact that heritage and monuments construct a way of understanding reality has led this article to examine the class dimension of heritage by examining three former factories which have been declared industrial heritage for how the industrial past is narrated and the way workers are portrayed within it: Battersea Power Station (London), the Gas Factory (Athens) and the El Águila Brewery (Madrid). This will be accomplished by analyzing relevant bibliography and narratives of monuments studied. A new urban design incorporates the industrial past of the city. Restoration of some buildings was based on architectural singularity or the uniqueness of the machines housed. Monumentalistic conceptions of industrial heritage that reduce factories to machines. The human perspective of industrialisation, the experience of work and of the workers, seems to be left out.